2023
DOI: 10.3390/ijms242015291
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Complexity of Neuromuscular Diseases: Insights from Human Pluripotent Stem Cell-Derived Neuromuscular Junctions

Morgan Gazzola,
Cécile Martinat

Abstract: Over the past 20 years, the use of pluripotent stem cells to mimic the complexities of the human neuromuscular junction has received much attention. Deciphering the key mechanisms underlying the establishment and maturation of this complex synapse has been driven by the dual goals of addressing developmental questions and gaining insight into neuromuscular disorders. This review aims to summarise the evolution and sophistication of in vitro neuromuscular junction models developed from the first differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…This work facilitated the development of more advanced models with physical separation between the pre-and post-synaptic compartments, hence supporting the formation of functional NMJs [308]. Later studies have shown that the addition of other cell types to the system, such as endothelial cells or astrocytes, leads to further improvement in NMJ development, functionality, and biomimicry [313][314][315]. The interactions between the different cell types are supported by using hydrogels as substrates, and the addition of extra chambers opens the possibility of modeling the interactions between the NMJ and other organs [314].…”
Section: Modeling Aging-related Neuromuscular Junction Degenerationmentioning
confidence: 88%
See 1 more Smart Citation
“…This work facilitated the development of more advanced models with physical separation between the pre-and post-synaptic compartments, hence supporting the formation of functional NMJs [308]. Later studies have shown that the addition of other cell types to the system, such as endothelial cells or astrocytes, leads to further improvement in NMJ development, functionality, and biomimicry [313][314][315]. The interactions between the different cell types are supported by using hydrogels as substrates, and the addition of extra chambers opens the possibility of modeling the interactions between the NMJ and other organs [314].…”
Section: Modeling Aging-related Neuromuscular Junction Degenerationmentioning
confidence: 88%
“…This feature enables the integration of sensors to monitor the cellular response to biophysical stimuli and drugs [311]. Park and coworkers produced one of the first microfluidic-based NMJ models using mouse embryonic stem cells to generate the motor neurons and C2C12 myoblasts to produce the myofibers [312,313]. This work facilitated the development of more advanced models with physical separation between the pre-and post-synaptic compartments, hence supporting the formation of functional NMJs [308].…”
Section: Modeling Aging-related Neuromuscular Junction Degenerationmentioning
confidence: 99%
“…The NMJ is thought to be a highly adaptable structure that can change its form and function. In mature muscles, the levels of physical activity are the primary factors that influence the function of the NMJ [ 25 , 31 , 58 ]. Traditionally, it was believed that the activation patterns of the skeletal muscle mediated by motor neurons were the primary drivers of NMJ plasticity and the resulting determination of the muscle fiber type.…”
Section: Nmj Morphologymentioning
confidence: 99%
“…Because of this and other complexities in CNS injuries, the current therapeutic options addressing SCI and its impact on the NMJ are limited. While rehabilitation and physical therapy aim to mitigate the functional consequences [ 2 , 30 ], there is a notable gap in strategies specifically targeting the repair and restoration of the NMJ [ 31 , 32 ]. This gap underscores the need for a comprehensive review that not only elucidates the existing challenges but also explores potential therapeutic options to address this critical void in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, myogenic maturation features such as sarcomeric striation and spontaneous contraction have been described using sphere-based cultures of myogenic progenitors derived from hiPSC (Hosoyama et al, 2014;Jiwlawat et al, 2017). Even though these methods significantly enhanced the general degree of maturation that myotubes can reach in vitro, achieving the formation of neuromuscular synapses similar in function and/or morphology to NMJs remained challenging (reviewed in Luttrell et al, 2021;Lynch et al, 2022;Gazzola and Martinat, 2023;Kim et al, 2023).…”
Section: Introductionmentioning
confidence: 99%